2007
DOI: 10.1007/s00464-007-9378-6
|View full text |Cite
|
Sign up to set email alerts
|

Best timing for thoracoscopic evacuation of retained post-traumatic hemothorax

Abstract: Videothoracoscopy must be considered the procedure of choice for the treatment of retained post-traumatic hemothorax. It is a safe and effective procedure allowing the successful treatment of up to 73.4% of patients. Best results are obtained when drainage is performed within the first five days after trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 28 publications
1
43
0
9
Order By: Relevance
“…No obstante, el enfoque diagnóstico y el tratamiento óptimo no están bien establecidos y se han propuesto múltiples estrategias; se sugiere que la cirugía videoasistida es una aproximación adecuada y exitosa en la mayoría de los casos 12,13 . El mejor momento para practicar este procedimiento está por establecerse, aunque en algunos trabajos se sugiere que los mejores resultados se obtienen cuando la toracoscopia se practica en los primeros cinco días después del evento 14,15 . Si se lograra establecer que la coagulación es un fenómeno temprano, se podría seleccionar un grupo de pacientes que se beneficiara de intervenciones diferentes a la toracostomía cerrada como el manejo inicial del hemotórax.…”
Section: Discussionunclassified
“…No obstante, el enfoque diagnóstico y el tratamiento óptimo no están bien establecidos y se han propuesto múltiples estrategias; se sugiere que la cirugía videoasistida es una aproximación adecuada y exitosa en la mayoría de los casos 12,13 . El mejor momento para practicar este procedimiento está por establecerse, aunque en algunos trabajos se sugiere que los mejores resultados se obtienen cuando la toracoscopia se practica en los primeros cinco días después del evento 14,15 . Si se lograra establecer que la coagulación es un fenómeno temprano, se podría seleccionar un grupo de pacientes que se beneficiara de intervenciones diferentes a la toracostomía cerrada como el manejo inicial del hemotórax.…”
Section: Discussionunclassified
“…Uniportal video-assisted thoracoscopic surgery in hemothorax visualization, a higher yield of detecting small injuries, less post-operative pain, improved lung function, shorter hospital stay and earlier recovery (2,5,7,8).…”
Section: Review Article On Thoracic Surgerymentioning
confidence: 99%
“…Since then, many authors described the use of this technique for diagnostic (diaphragmatic lesions) and therapeutic (hemothorax in penetrating chest trauma) options (13,14). However, only in the late 1990s, due to technical advances, its use became worldwide popular and VATS gained a primary position in the care of thoracic trauma patients (7,15). Villavicencio et al (16) demonstrated that thoracoscopy may be used safely and successfully in assessment of clotted or persistent hemothorax and in empyema drainage; according to their data, 90-95% of patients with posttraumatic hemothorax are treated conservatively or with tube thoracostomy only, 20% develop later a clotted or a persistent loculated hemothorax after drainage and 40% of them require eventually a surgical procedure.…”
Section: Multiportal Vats Strategy: Basic Conceptsmentioning
confidence: 99%
See 2 more Smart Citations